Effects of Metformin Administration on Behavioral and Biochemical Parameters in a Familial Hypercholesterolemia Mouse Model - Natália Baltazar do Nascimento; Hémelin Resende Farias; Tainá Schons; Matheus Scarpatto Rodrigues; Jade de Oliveira (2023)
Abstract Background Low‐density lipoprotein (LDL) is responsible for the transport of cholesterol to peripheric tissues (Cortes et al. 2014), and it enters the cells via LDL receptors (LDLr) (Luo, Yang, Song 2020). Cholesterol metabolism alterations, i.e., hypercholesterolemia are well‐known cardiovascular risk factors and have also been linked to cognitive and behavioral alterations (De Oliveira et al. 2011, Sparks et al. 1990, WHO 2008). Familial hypercholesterolemia (FH) is a prevalent disease caused by dysfunctions of cholesterol metabolism (Akioyamen et al. 2017), and several reports show its connection to neuroinflammation (Ariza et al. 2016, De Oliveira et al. 2020). Recent studies associate mTOR inhibition with conservation of blood‐brain barrier integrity, cognitive damage attenuation, and systemic and cerebral inflammation reduction in dementia and FH animal models (Jahrling et al. 2018, Van Skike et al. 2018). In this regard, Metformin presents critical therapeutic potential because it inhibits mTOR through AMPK. Objective Evaluation of Metformin treatment on cognitive disturbances and central and peripheric biochemical parameters in C57BL/6 LDLr deficient (LDLr‐/‐) mice. Method LDLr‐/‐ and wild‐type (WT) male mice (3‐month‐old, 20‐3 g) received a daily oral administration via gavage of Metformin (200 mg/kg) or Saline for 30 days. All animals were weighed weekly. Mice were submitted to behavioral tasks in the last week of treatment. Following the last day of treatment, animals fasted for 12 hours and were euthanized by cardiac exsanguination. Heparinized plasma was used to determine total cholesterol and triglyceride levels. Another cohort of animals was perfused with paraformaldehyde to collect fixed total brains, which were used in immunofluorescence assays for labeling glial fibrillary acidic protein (GFAP). Result LDLr‐/‐ mice showed higher total cholesterol levels compared to WT groups. Metformin treatment increased triglyceride levels and decreased total body weight in LDLr‐/‐ mice in comparison to Saline administration. LDLr‐/‐ mice showed hyperlocomotive activity, cognitive damage, and a depressed phenotype, which was in parts attenuated by Metformin treatment. Metformin treatment ameliorated astrogliosis in the hippocampus of LDLr‐/‐ mice. Conclusion Metformin treatment showed a promising effect on the memory impairment and astrocyte reactivity observed in LDLr‐/‐ mice, which was not via a cholesterol‐lowering outcome.